2013
DOI: 10.1002/gcc.22092
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐genome paired‐end analysis confirms remarkable genomic stability of atypical teratoid/rhabdoid tumors

Abstract: in Wiley Online Library (wileyonlinelibrary.com).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…Across 35 of these SMARCB1-deficient cancers, there were essentially no other recurrent mutations and in two of the cancers there were no other identified mutations at all. The same conclusion was reached in other studies as well(53, 54). Given the paucity of other mutations and the extremely rapid onset of cancer in mouse models, these findings seem to suggest that SMARCB1-deficiency may not cause cancer via defects in DNA repair but rather due to epigenetic alterations such as disruption of chromatin-based contributions to control of cell fate.…”
Section: Introductionsupporting
confidence: 90%
“…Across 35 of these SMARCB1-deficient cancers, there were essentially no other recurrent mutations and in two of the cancers there were no other identified mutations at all. The same conclusion was reached in other studies as well(53, 54). Given the paucity of other mutations and the extremely rapid onset of cancer in mouse models, these findings seem to suggest that SMARCB1-deficiency may not cause cancer via defects in DNA repair but rather due to epigenetic alterations such as disruption of chromatin-based contributions to control of cell fate.…”
Section: Introductionsupporting
confidence: 90%
“…Genetic alterations in subunits of the SWI/SNF complex are quite common and occur in up to 20% of all human cancers [34, 35]. According to accumulating evidence, biallelic inactivation of the SMARCB1 gene has repeatedly been found to be the almost sole driving genetic alteration in AT/RTs [5, 7, 8, 36]. A variety of mechanisms, such as deletions, mutations, and loss of heterozygosity, are responsible for SMARCB1 inactivation in AT/RTs [37].…”
Section: Discussionmentioning
confidence: 99%
“…The SMARCB1 protein is a core subunit of the switch/sucrose non-fermentable chromatin remodeling (SWI/SNF) complex that regulates the expression of thousands of genes [6]. High-resolution genomic analysis and whole exome sequencing studies identified extremely low mutation rates for genes other than the biallelic inactivation of SMARCB1 in rhabdoid tumors [5, 7]. A recent study in which whole genome sequencing was undertaken for many AT/RT samples also reported rare recurrent mutations aside from the mutations in SMARCB1 [8].…”
Section: Introductionmentioning
confidence: 99%